The role of institutional infrastructures in financial inclusion-growth relations: Evidence from SSA - Kazeem Bello Ajide; Ibrahim Dolapo Raheem; Olorunfemi Yasiru Alimi; Simplice Asongu (African Governance and Development Institute (AGDI), 2020)
This paper investigates the role of institutional infrastructures in the financial inclusion-growth nexus for a panel of twenty countries in sub-Sahara Africa (SSA).Employing the System Generalized Method of Moments (GMM), the following insightful outcomes are established. First, while there is an unrestricted positive impact of physical access to ATMs and ICT measures of financial inclusion on SSA's growth but only the former was found significant. Second, the four institutional components via economic, political, institutional and general governances were also found to be growth-spurring. Lastly, countries with low levels of real per capita income are matching up with other countries with high levels of real income per capita. The empirical evidence of some negative net effects and insignificant marginal impacts are indication that imperfections in the financial markets are sometimes employed to the disadvantage of the poor. On the whole, we established positive effects on growth for the most part. The positive effects are evident because the governance indicators compliment financial inclusion in reducing pecuniary constraints hindering credit access and allocation to the poor that deteriorate growth.
Keywords: G20; I10; O40; P37; 330; Financial Inclusion; Economic Growth; Governance; System Generalized Method of Moments (GMM)